2013
DOI: 10.1111/dmcn.12224
|View full text |Cite
|
Sign up to set email alerts
|

Vocational rehabilitation services and employment outcomes for adults with cerebral palsy in the United States

Abstract: Aim The aim of this study was to examine the relationship between vocational rehabilitation services provided and work outcomes among people with cerebral palsy (CP), taking in to account demographic characteristics. Method From the US Department of Education Rehabilitation Service Administration Case Service Report (RSA‐911) database, data from 3162 individuals with CP (1820 males [57.6%] and 1342 females [42.4% age range 16–54y) whose cases were closed in 2009, were used in this study. A total of 1567 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…7,21 In our analyses, we did not differentiate competitive from sheltered employment, which may have precluded such an association. A high education level has found to be significant for achieving competitive employment in adults with CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,21 In our analyses, we did not differentiate competitive from sheltered employment, which may have precluded such an association. A high education level has found to be significant for achieving competitive employment in adults with CP.…”
Section: Discussionmentioning
confidence: 99%
“…A high education level has found to be significant for achieving competitive employment in adults with CP. 7,21 In our analyses, we did not differentiate competitive from sheltered employment, which may have precluded such an association. However, the figure shows that the most substantial contrast between competitive and sheltered employment lies between subgroups with different education levels.…”
Section: Discussionmentioning
confidence: 99%
“…People with multiple sclerosis (MS) face unique barriers to employment, since MS is associated with a wide range of physical, cognitive, and emotional symptoms that appear episodically and unpredictably (Roessler & Rumrill, 2003;Rumrill et al, 2013). In addition, a number of researchers have reported that individuals with cerebral palsy (CP) continue to experience significantly lower rates in getting and keeping employment in comparison to individuals without disabilities (Huang et al, 2013;Magill-Evans, Galambos, Darrah, & Nickerson, 2008). As a final example, the National Spinal Cord Injury Statistic Center reported information on 28,450 individuals with SCI in the National Spinal Cord Injury Database.…”
mentioning
confidence: 99%
“…Huang et al. describe factors that contribute to employment outcomes in adults with CP who received vocational rehabilitation services, and provide some insights into the complexity of achieving such outcomes . The role of higher education and increased services in achieving employment are particularly germane to health care providers.…”
mentioning
confidence: 99%
“…Therapy services, called related services in school systems, which support educational outcomes are mandated by law. Activities of daily living, expressive language skills (which can be provided by augmentative devices when speech is not possible), social skills, and arm/hand use are routine therapy outcomes for occupational and physical therapists and speech‐language pathologists that have been identified as important to future employment . Driver education and/or use of community mobility systems when available are aspects of work that can be initiated in the school system, especially when vocational rehabilitation services are part of transition planning.…”
mentioning
confidence: 99%